Analysis of CRISPR-Cas systems in Gardnerella suggests its potential role in the mechanisms of bacterial vaginosis. (December 2020) - Ruiz-Hernández, Ubaldo Emilio; Pelcastre-Rodriguez, Leda Ivonne; Cabrero-Martínez, Omar Alejandro; Hernández-Cortez, Cecilia; Castro-Escarpulli, Graciela
Graphical Abstract: Highlights: CRISPR-Cas systems are highly distributed within the genus Gardnerella Hypervariability of spacers can be useful for typing purposes in Gardnerella spp. CRISPR-Cas based studies could shed light of its niche among vaginal microbiota Abstract: Bacterial vaginosis (BV) is the principal cause of vaginal discharge among women, and it can lead to many comorbidities with a negative impact in women's daily activities. Despite the fact that the pathophysiological process of BV remains unclear, great advances had been achieved in determining consequences of the shift in the vaginal community, and it was defined that Gardnerella spp., plays a key role in the pathogenesis of BV. Interactions of vaginal phage communities and bacterial hosts may be relevant in eubiosis/dysbiosis states, so defense mechanisms in Gardnerella spp., against phage infections could be relevant in BV development. In this study, we analyzed CRISPR-Cas systems among the 13 Gardnerella species recently classified, considering that these systems act as prokaryotic immune systems against phages, plasmids, and other mobile genetic elements. In silico analyses for CRISPR-Cas systems mining over the 81 Gardnerella spp., strains genomes analyzed led to the identification of subtypes I-E and II-C. Spacers analyses showed a hypervariable region across species, providing a high resolution level in order to distinguish clonality in strains, which was supported with phylogenomic analyses based on Virtual Genomic Fingerprinting. Moreover, most of the spacers revealed interactions between Gardnerella spp., strains and prophages over the genus. Furthermore, virulence traits of the 13 species showed insights of potential niche specificity in the vaginal microbiome. Overall, our results suggest that the CRISPR-Cas systems in the genus Gardnerella may play an important role in the mechanisms of the development and maintenance of BV, considering that the Gardnerella species occupies different niches in the vaginal community; in addition, spacer sequences can be used for genotyping studies.